**Chapter 1**

**Grade 7 Integer Review:**

(+4)-(-4)

This means you have a zero pair

(+4)-(-4)=0

(+6) + (-2) = +4

Positive 6 and Negative 2 = Positive 4

You have 6 and you owe 2 = have 4

Making Zero Pairs:

-6=+6

-21=+21

-42=+42

-65=+65

-11=+11

-14=+14

-63=+63

**Chapter 2**

**Multiplying Integers:**

SIGN RULE:

Even: When you have a even number of

**factors the product is**

*negative***.**

*positive*Odd: When you have a odd number of

**the product is**

*negative**.*

**negative**(+2)x(-3)=

2 groups of (-3)=(-6)

(+2)x(+3)

2 groups of (+3)=(+6)

(-2)x(+3)

2 groups of (+3)=-6

(-2)x(-3)=

2 groups of (-3)=6

**Chapter 3**

**Dividing integers:**

SIGN RULE:

If you have no negative or an even number of negative signs in a division question, the quotient is positive.

**There are 2 types of division:**

One of them is,

Partitive division:

Partitive division is making parts.

*Example:*

6 divided by 2= 3

6 divided by -2= -3

The Other on is,

Quotative division:

Quotative division is sharing your total, with groups.

*Example:*

(-6) divided by 2= -3

6 divided by (-2)= +3

**Chapter 4**

**Order Of Operations:**

Use Badmas.

B =stands for brackets

E =stands for exponents

D =stands for division

M =stands for multiplication

A =stands for addition

S =stands for subtraction

First solve any brackets, then exponents, then any divide, then multiply, then add, and lastly, subtract.

If I had to solve this problem:

(+5) x (-3) + (-6) ÷ (+3)=

First I would put brackets around, (-6)÷(+3). Then solve it.

[(-6)÷(+3)]=(-2)

Now the question would be:

(+5) x (-3) + (-2)=

Using the BEDMAS rules, exponents are next, but there is none. So we move on to multiplication:

(+5) x (-3)= (-15)

The question is now:

(-15) + (-2)=

Lastly you will answer it:

(-15) + (-2)= (-17)

## No comments:

## Post a Comment